World investment report 2008 : (United nations, 2008)
The World Investment Report 2008 presents the latest data on foreign direct investment (FDI) and traces global and regional trends in FDI and in international production by transnational corporations (TNCs). This year's report puts a special focus on the role of TNCs in meeting the huge needs of developing countries for infrastructure such as roads, ports, water, gas and electricity supply, and telecommunications. Drawing on unique data, this year, the Report examines the universe of the largest TNCs investing in infrastructure industries and the increasing role of TNCs from the South in contributing to infrastructure in other developing economies. The Report explores how the participation of TNCs brings benefits, but also entails risks and costs. It considers how the mix of public and private (including TNC) involvement can help spur foreign investment and knowledge transfer to countries that need such inflows.